Relationship Between Metabolic Syndrome and Periodontal Diseases According to Socio-Demograpic Variables - Ah-Reum Shin; Yi Sub Kwak; Hye-Young Kim (운동과학)
PURPOSE Due to the changes in the Westernized diet and lifestyle, the number of metabolic syndrome and periodontal disease cases in Korean adults is on the rise. Since recently, however, considering the increasing social awareness of the importance of health Korean adults and the necessity of establishing policies for oral health promotion, it has become important to establish basic data on the formulation of a national oral health promotion policy by identifying the relationships among metabolic syndrome, social factors, and periodontal disease. METHODS The obtained data were analyzed using the data of the 6th National Health and Nutrition Survey (2015), which are representative of the national population, and of those who are over 19 years old who have completed the metabolic syndrome survey and oral examination. The statistical analysis of the data was performed using the SPSS (PASW statistics) 22.0 statistical program and chi square test and binomial logistic analyses. RESULTS The main results of the study are as follows. First, for the metabolic syndrome judgment factors, the prevalence of periodontal disease was higher in the order of the metabolic syndrome group, metabolic syndrome risk group, and normal group. The metabolic syndrome factors showed that the distribution of the periodontal disease prevalence rate was different. Second, the results of the analysis of the effect of periodontal disease through binomial logistic regression analysis showed that in the normal group, metabolic syndrome risk group, and metabolic syndrome group, sex, age, and income level exerted an influence on periodontal disease, and such influence was statistically significant. CONCLUSIONS In conclusion, the results of this study can be used as basic data for the formulation of a comprehensive policy for the development of programs for the prevention of metabolic syndrome and periodontal disease and the reduction of the social problems caused by chronic diseases